Proceedings of the 5th International Conference on Electronic Commerce - ICEC '03 2003
DOI: 10.1145/948005.948060
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing consumer behavior at retailers with hybrid distribution channels

Abstract: Retailers with multiple distribution channels are increasingly gaining market shares compared to Internet-only retailers. However, a lack of research explaining consumers' purchasing behavior in a multi-channel context can be identified.This paper discusses examples of multi-channel strategies and describes in detail the case of an online retailer who aims at measuring the interrelation between the sales channel Internet and a physical branch network. Based on the analysis of the retailer's transaction data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…From a consumer perspective, Mcgoldrick et al(2007) claimed that multi-channel integration quality is a "seamless" shopping experience provided by retailers to customers, who can switch between channels freely at any time according to their needs. Teltzrow et al(2003) found that multi-channel retailers are better able to meet the diverse needs of consumers and cater to their consumption habits than single-channel retailers. In fact, since multi-channel integration quality involves several aspects, some scholars define it by considering both consumer and business perspectives.…”
Section: Multichannel Integration Qualitymentioning
confidence: 99%
“…From a consumer perspective, Mcgoldrick et al(2007) claimed that multi-channel integration quality is a "seamless" shopping experience provided by retailers to customers, who can switch between channels freely at any time according to their needs. Teltzrow et al(2003) found that multi-channel retailers are better able to meet the diverse needs of consumers and cater to their consumption habits than single-channel retailers. In fact, since multi-channel integration quality involves several aspects, some scholars define it by considering both consumer and business perspectives.…”
Section: Multichannel Integration Qualitymentioning
confidence: 99%
“…In today's age, where digital technology is inevitable and information is amply available, consumers can learn about others' experiences through their smartphones and subsequently experience the products in the digital world ahead of purchasing them. Many consumers use the internet to collect information on products and brands before making purchases offline (Venkatesan et al, 2007;Teltzrow et al, 2007). Various stimuli, including brands' messages on social media, become the primary sources of information for consumers to make purchasing decisions.…”
Section: Zero Moment Of Truth (Zmot)mentioning
confidence: 99%
“…Providing multiple channels to customers throughout their shopping journeys has been mostly associated with positive consumer behavior (Pauwels and Neslin 2015;Teltzrow et al 2007). More shopping alternatives could serve customers better, according to their distinct needs and shopping situations (Wang and Goldfarb 2016).…”
Section: Multichannel Options For Social Coupon Redemption Effects On...mentioning
confidence: 99%